Parent Involvement in Homework: A Research Synthesis - Patall, Erika A.; Cooper, Harris; Robinson, Jorgianne Civey (Review of Educational Research, 2008)
New emphasis is being placed on the importance of parent involvement in children’s education. In a synthesis of research on the effects of parent involvement in homework, a meta-analysis of 14 studies that manipulated parent training for homework involvement reveals that training parents to be involved in their child’s homework results in (a) higher rates of homework completion, (b) fewer homework problems, and (c) possibly, improved academic performance among elementary school children. A meta-analysis of 22 samples from 20 studies correlating parent involvement and achievement-related outcomes reveals (a) positive associations for elementary school and high school students but a negative association for middle school students, (b) a stronger association for parent rule-setting compared with other involvement strategies, and (c) a negative association for mathematics achievement but a positive association for verbal achievement outcomes. The results suggest that different types of parent involvement in homework have different relationships to achievement and that the type of parent involvement changes as children move through the school grades.